The Completion to the Profession Active is Modeled of Future Economists in the Mountain Conditions of Environment - Galushchak, Iryna (Journal of Vasyl Stefanyk Precarpathian National University, 2014)
The article analyzes the economics of the training of the future to the profession, the analysis works on the phenomenon of commitment to the profession, defines the dominant components that directly affect the process of professional economics in working conditions in mountainous regions